Aspectos psicossociais do trabalho e qualidade do sono entre docentes de educação superior - Freitas , Aline Macedo Carvalho (2018)
This study provides to evaluate the association between the psychosocials aspects of work and sleep quality between professors of a public university from Bahia. It’s a epidemiologic study, cross-sectional, realized with 423 professors randomly selected for department and kind of employee. For date collection, used a standardized questionnaire, private and self-applicable, constituted for nine questions blocs. The psychosocials aspects were availed for Job Content Questionnaire (JCQ) and the sleep quality was measured for scale Mini-Sleep Questionnaire (MSQ).The covariables of interest were that belonging to blocs with general information about the work, the habits of life and health and the general identification. Realized a descriptive analyze, bivariate and multivariate. This study, the prevalence estimated of bad sleep quality was 61,3% . The difficult to sleep, wake up tired, wake up headache and don’t have time to sleep during the day were the complaints more frequently between the professors. They were statistically associated with bad sleep quality, the variations: irregular time and/or insufficient for the practice of recreation activity, sleep hours ≤ 6 hours, musculoskeletal pain, headache and high requirement experience of Demand-Control Model (DMC). The results indicate the psychosocial aspects of work are associated factors with the bad sleep quality. On analyze of effects modifiers, it was found that the practical variable of physical activity modified the main association in test. In the final analyze, the high exigency and passive work were associate experience to bad sleep quality between the professors didn’t practice physic activity. However, is possible to confirm the psychosocial aspects of work are related to negative effects on sleep quality of professors.